The Interplay of Financial Literacy on the Financial Behavior and Well-being of Young Adults: Evidence from Nigeria - Sajuyigbe, Ademola Samuel; Adegun, Emmaunel Aderinola; Adeyemi, Francis; Johnson, Adebayo Akanbi; Oladapo, John Tawiah; Jooda, Dayo Taiwo (Jurnal Ilmu Ekonomi Terapan, 2024)
The financial stability of young adults worldwide is under threat due to widespread impulsive online purchasing and the economic strain brought on by the COVID-19 pandemic. This study, therefore, examines the role of financial literacy as a mediator between financial behavior and the financial well-being of young adults, specifically in Nigeria. The research involved 120 respondents, 60 undergraduate and 60 postgraduate students from three selected universities in Western Nigeria. Information was gathered through a structured questionnaire. Data analysis was conducted using Structured Equation Modeling with STATA version 15. The findings reveal a positive association between financial behavior and financial well-being, although this relationship lacks statistical significance. However, significant positive correlations are observed between financial literacy (FL) and financial well-being (FW), as well as between financial behavior (FB) and financial literacy (FL). Furthermore, the analysis uncovers a positive indirect effect of financial literacy on the relationship between financial behavior and financial well-being. This suggests that while the direct link between financial behavior and well-being may be weak, improved financial behavior can indirectly enhance well-being through heightened financial literacy. In essence, the study underscores the crucial role of financial literacy in improving young adults' financial behaviors and well-being. By investing in education, support services, and policies that encourage positive financial behaviors, both individuals and policymakers can collaborate toward constructing a more financially secure future for the younger generation.